Предмет: Алгебра, автор: Аноним

149. Доведіть тотожність: 1) 4 (2 - 3m) - (6 - m) - 2 (3m + 4) = -17m - 6; 2) a + b – 10ab = 2а (3 - b) - 36 (а - 2) - 5 (ab + a + b): 3) 6 (5а - 3) + (10 - 20а) - (6а - 4) = 5а - (3а - (2а - 4).​

Ответы

Автор ответа: timurahmetzyanov50
1

1)

4 (2 - 3m) - (6 - m) - 2 (3m + 4) = -17m - 6

8 - 12m - 6 + m - 6m - 8 + 17m + 6 = 0

- 12m + m - 6m + 17m = 6 + 8 - 6 - 8

0 = 0

==================================

2)

a + b – 10ab = 2а (3 - b) - 36 (а - 2) - 5 (ab + a + b)

a + b – 10ab = 6a - 2ab - 36a + 72 - 5ab - 5a - 5b

- 6a + 36a + a + 5a = 10ab - 2ab - 5ab - b - 5b + 72

36a = 3ab - 6b + 72

3 ( ab - 2b - 12a) + 72 = 0

==================================

3)

6 (5а - 3) + (10 - 20а) - (6а - 4) = 5а - (3а - (2а - 4)

30a - 18 + 10 - 20a - 6a + 4 - 5a + 3a - 2a + 4 = 0

0 = 0

Автор ответа: 198401300
2

Объяснение:

Решение смотри во вложении

Приложения:
Похожие вопросы